Multigroup Moderation Test in Generalized Structured Component Analysis - Mulyanto, Angga Dwi; Solimun, Solimun; Wardhani, Ni Wayan Surya; Suharno, Suharno (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2016)
Generalized Structured Component Analysis (GSCA) is an alternative method in structural modeling using alternating least squares. GSCA can be used for the complex analysis including multigroup. GSCA can be run with a free software called GeSCA, but in GeSCA there is no multigroup moderation test to compare the effect between groups. In this research we propose to use the T test in PLS for testing moderation Multigroup on GSCA. T test only requires sample size, estimate path coefficient, and standard error of each group that are already available on the output of GeSCA and the formula is simple so the user does not need a long time for analysis.